Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the equation [tex]\(6(9 y - 1) - 10(5 y) - 3 y = -4(2 y - 12) + 8(y - 6)\)[/tex], follow these steps:
### Step 1: Distribute the constants within the parentheses.
Expand both sides of the equation:
[tex]\[ 6(9 y - 1) = 6 \cdot 9 y - 6 \cdot 1 = 54 y - 6 \][/tex]
[tex]\[ -10(5 y) = -10 \cdot 5 y = -50 y \][/tex]
[tex]\[ -4(2 y - 12) = -4 \cdot 2 y + 4 \cdot 12 = -8 y + 48 \][/tex]
[tex]\[ 8(y - 6) = 8 \cdot y - 8 \cdot 6 = 8 y - 48 \][/tex]
So the equation now looks like:
[tex]\[ 54 y - 6 - 50 y - 3 y = -8 y + 48 + 8 y - 48 \][/tex]
### Step 2: Combine like terms on both sides.
Combine the [tex]\( y \)[/tex] terms and constant terms respectively:
[tex]\[ 54 y - 50 y - 3 y - 6 = -8 y + 8 y + 48 - 48 \][/tex]
[tex]\[ (54 y - 50 y - 3 y) - 6 = 0 \][/tex]
[tex]\[ 1 y - 6 = 0 \][/tex]
### Step 3: Isolate the variable [tex]\( y \)[/tex].
Add 6 to both sides to solve for [tex]\( y \)[/tex]:
[tex]\[ y - 6 + 6 = 0 + 6 \][/tex]
[tex]\[ y = 6 \][/tex]
Thus, the value of [tex]\( y \)[/tex] is:
[tex]\[ \boxed{6} \][/tex]
### Step 1: Distribute the constants within the parentheses.
Expand both sides of the equation:
[tex]\[ 6(9 y - 1) = 6 \cdot 9 y - 6 \cdot 1 = 54 y - 6 \][/tex]
[tex]\[ -10(5 y) = -10 \cdot 5 y = -50 y \][/tex]
[tex]\[ -4(2 y - 12) = -4 \cdot 2 y + 4 \cdot 12 = -8 y + 48 \][/tex]
[tex]\[ 8(y - 6) = 8 \cdot y - 8 \cdot 6 = 8 y - 48 \][/tex]
So the equation now looks like:
[tex]\[ 54 y - 6 - 50 y - 3 y = -8 y + 48 + 8 y - 48 \][/tex]
### Step 2: Combine like terms on both sides.
Combine the [tex]\( y \)[/tex] terms and constant terms respectively:
[tex]\[ 54 y - 50 y - 3 y - 6 = -8 y + 8 y + 48 - 48 \][/tex]
[tex]\[ (54 y - 50 y - 3 y) - 6 = 0 \][/tex]
[tex]\[ 1 y - 6 = 0 \][/tex]
### Step 3: Isolate the variable [tex]\( y \)[/tex].
Add 6 to both sides to solve for [tex]\( y \)[/tex]:
[tex]\[ y - 6 + 6 = 0 + 6 \][/tex]
[tex]\[ y = 6 \][/tex]
Thus, the value of [tex]\( y \)[/tex] is:
[tex]\[ \boxed{6} \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.